Innovative design of Islamic geometric patterns in living spaces: parametric and digital design with grasshopper and ControlNet - Ma, Yue; Mohd Ariffin, Noor Fazamimah; Abdul Aziz, Faziawati; He, Xiao (Birkhauser, 2024)
In non-Muslim countries with an Islamic historical background, Islamic geometric patterns (IGPs) are significant for reflecting the history, identity, and culture of the local Muslim communities. However, effectively communicating these patterns with local cultures remains a pressing issue. This study focuses on Donglianhua Village, a Muslim community in Weishan County, Yunnan Province, China, employing the Grasshopper plugin in Rhino software, principles of shape grammar, and digital technologies, including Stable Diffusion and ControlNet, for the design of IGPs. A subsequent satisfaction survey conducted with 219 villagers yielded an average satisfaction score of 3.583, indicating the design’s success and broad acceptance. This study demonstrates the potential of parametric design and digital technology interventions in facilitating cultural dialogue and integration.